Fluoride exposure from ingested toothpaste in 4–5-year-old Malaysian children - Tan BS, Razak IA. (Blackwell Synergy, 2005)
The aim of this study was to assess (by direct determination) the fluoride (F) exposure from ingested toothpaste among 4–5-year-old Malaysian children.